Pelatihan Pengembangan Bahan Ajar Diferensial Model Apos Berbantuan Geogebra - Hanifah, Hanifah; Utari, Tria (EDUPEDIA Publisher, 2022)
The low students’ score of mathematics is influenced by learning that is not insightful to students. Teachers have not implemented learning that has been set for students as suggested by the 2013 curriculum. In addition, teachers have also not utilized technology, especially digital technology in learning. One of the reasons is that teachers have not been able to develop teaching materials for learning models that are set for students and use technology. One of the learning models set for students is the APOS model. To train teachers to compile teaching materials, the implementation of workshop on the development of differential teaching materials using APOS model combined GeoGebra. This workshop was given to SMA/SMK/MA math teachers in Bengkulu City. The response of the participants after participating in the training was in the very good category as much as 95.45%. Participants said this activity was very useful for them in making teaching materials.